Wild Oats : sowing vs. reaping - Shefsky, Lloyd E.; Barnett, Bob; Whitaker, Scott T. ([London] : SAGE, 2016)
The case highlights Mike Gilliland, who built a single organic foods store in 1987 in Boulder, Colorado, into Wild Oats Markets, a chain of natural foods stores that by 2001 had annual sales of $1 billion and stores in 38 states. The case includes a history of the natural foods business and explores why Gilliland's timing was so favourable.
Originally Published in: Shefsky, L., Barnett, B. & Whitaker, S. T. (2010). Wild Oats: Sowing vs. Reaping. 5-110-007. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Wild Oats (Firm); Business planning -- Case studies; Corporations -- Growth -- Case studies